Reading Cicero’s Final Years. Receptions of the Post-Caesarian Works up to the Sixteenth Century – with two Epilogues - Velden, Bram van der; Pieper, Christoph (2020)
This volume contributes to the ongoing scholarly debate regarding the reception of Cicero. It focuses on one particular moment in Cicero’s life, the period from the death of Caesar up to Cicero’s own death. These final years have shaped Cicero’s reception in an special way, as they have condensed and enlarged themes that his life stands for: on the positive side his fight for freedom and the republic against mighty opponents (for which he would finally be killed) on the other hand his inconsistency in terms of political alliances and tendency to overestimate his own influence. For that reason, many later readers viewed the final months of Cicero's life as his swan song, and as representing the essence of his life as a whole.The fixed scope of this volume facilitates an analysis of the underlying debates about the historical character Cicero and his textual legacy (speeches, letters and philosophical works) through the ages, stretching from antiquity itself to the present day. Major themes negotiated in this volume are the influence of Cicero’s regular attempts to anticipate his later reception the question of whether or not Cicero showed consistency in his behaviour his debatable heroism with regard to republican freedom and the interaction between philosophy, rhetoric and politics.